Image-based supervision of a periodically working machine - Frank, Mario; Hamprecht, Fred (Pattern analysis and applications, 2013)
Most industrial robots perform a periodically repeating choreography. Our aim is to detect disturbances of such a periodic process by a visual inspection system that can be trained with a minimum of human effort and interaction. We present a solution that monitors the robot with a time-of-flight 3D camera. Our system can be trained using a few unperturbed cycles of the periodic process. More specifically, principal components are used to find a low-dimensional approximation of each frame, and a One-Class Support Vector Machine is used for one-class learning. We propose a novel scheme for automatic parameter tuning, which exploits the fact that successive images of the training class should be close in feature space. We present exemplary results for a miniature robot setup. The proposed strategy does not require prior information on the dimensions of the machine or its maneuvering range. The entire system is appearance-based and hence does not need access to the robot’s internal coordinates.
Published: 30 September 2011
Gesehen am 26.04.2021